Making Environmentally Friendly Liquid Dish Soap to Increase Student Productivity In The Field of Entrepreneurship - Putri, Nabila Amelia Kurnia; Maiyanti, Aziza Anggi; Anggraini, Atika; Wulandari, Ratna Wahyu; Cengiz, Korhan (Islamic Journal of Integrated Science Education (IJISE), 2025)
This research aims to increase students’ knowledge and skills in producing environmentally friendly liquid dish soap while developing entrepreneurial aspects. The process of making this soap uses chemicals such as texapon, salt, citric acid, and other ingredients that are processed with structured methods to produce quality and environmentally safe products. The results showed that this eco-friendly dish soap is not only effective in cleaning dirt, but also has economic value that can be developed as a business opportunity. This product has the potential to become a business with high competitiveness because it offers environmentally friendly advantages that are in demand by the market. In addition, this innovation also equips students with entrepreneurial skills, such as production management and marketing, which can help them achieve economic independence. Thus, this research has a positive impact both in terms of economy and environmental preservation.